Knowledge, attitude and practices regarding prevention of dengue in an urban area of Central India - Khobragade, Ashish Wasudeo; Meshram, Tarachand Tukaram (International Journal Of Community Medicine And Public Health, 2021)
Background: Dengue is vector borne disease transmitted by Aedes mosquito. Basic vector biology and its knowledge regarding prevention among people are important for the control of dengue outbreak. Methods: 400 houses were selected from dengue outbreak area. Each house was visited and breeding sites were searched and eliminated simultaneously. Face to face interview was conducted to assess knowledge, attitude and practices among people regarding prevention of dengue. Results: 25% of the study participants were not using personal protection to prevent against mosquito bite. Conclusions: Knowledge regarding dengue prevention was average among study participants although they had good attitudes and satisfactory practices.